2020
DOI: 10.1097/md.0000000000019796
|View full text |Cite
|
Sign up to set email alerts
|

Correlation study between serum neuro-specific enolase and gastric and colorectal cancers

Abstract: This study investigated the diagnostic value of preoperative serum neuro-specific enolase (NSE) in gastric cancer (GC) and colorectal cancer (CRC), and the diagnostic viability of combined serum NSE, carcinoembryonic antigen (CEA), cancer antigen (CA)19-9, and CA242. Patients with GC and CRC, and a healthy control group (n = 666 and 266, respectively) were compared with regard to NSE, CEA, CA19-9, and CA242 serum levels. NSE was analyzed for associations with clinicopathological parameters. To estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…On the other hand, decreased CDX2 expression is associated with poor differentiation and MMR deficiency in colorectal cancer 17 . In addition, it has been reported that elevated neuron‐specific enolase levels are seen in patients with advanced colorectal cancer 18 . Thus, although the patient had to be diagnosed with cancer of unknown primary origin, as lower gastrointestinal endoscopy was not performed, and the results of MMR deficiency‐related staining were inconclusive, it was assumed that colorectal cancer was likely to be the primary disease.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, decreased CDX2 expression is associated with poor differentiation and MMR deficiency in colorectal cancer 17 . In addition, it has been reported that elevated neuron‐specific enolase levels are seen in patients with advanced colorectal cancer 18 . Thus, although the patient had to be diagnosed with cancer of unknown primary origin, as lower gastrointestinal endoscopy was not performed, and the results of MMR deficiency‐related staining were inconclusive, it was assumed that colorectal cancer was likely to be the primary disease.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study showed sCEA is not independent factor while tCEA is for CRC ofⅠ~Ⅲ stage by multivariate analysis [8].Because the role of only preoperative serum for CRC has controversial issues, combined preoperative CEA and other tumor biomarkers are suggested [17,19,[34][35][36][37][38][39][40]. In this study of more recruited patients in 0&Ⅰ~Ⅳ, sCEA and tCEA are prognostic factors but not independent factors in CRC of Ⅲ~Ⅳ stages while combined CEA is an independent factor in advanced CRC by univariate and multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…During EMT, epithelial-like cancer cells transform to migratory and invasive mesenchymal-like cancer cells, acquiring a variety of characteristics such as self-renewal, self replication, differentiation and invasion of stroma ( 22 ). Neuroendocrine differentiation characterizes GC, and NSE, an enzyme specific to neuroendocrine cells, is a predictive and sensitive biomarker in GC ( 23 ). Studies have shown that down-regulating the expression of NSE gene can increase the expression of NM23 and E-cadherin, thereby inhibiting the proliferation and invasion of GC.…”
Section: Mechanism Of Gc Brain Metastasismentioning
confidence: 99%